VOLTAMMETRIC STUDY OF ELECTROCHEMICAL SENSORS USING BISMUTH-FE3O4 MODIFIED CARBON PASTE ELECTRODE IN DETECTING METAL ION MN (II) LEVELS IN WATER - Hanif Abiyyu, Irfan
Manganese is an essential trace mineral that is directly related to the functioning of several important metabolic processes within the human body. Manganese is processed into various important objects such as dry batteries, the steel industry, and electronic devices in the metal processing industry. Manganese waste if it exceeds the threshold can become a pollutant that is harmful to the aquatic environment and living things. Therefore, the determination of metal ion Mn2+ levels is important to do. Several methods have been reported for manganese analysis including AAS, MP-AES, ICPMS, and XRF. However, the method has weaknesses such as instrument procurement, operating cost, and spare parts being relatively expensive and difficult to order, also requires complex sample preparation. One alternative method that can be used is the voltammetric method that offers fast, selective, sensitive, and inexpensive measurements. In this study a voltammetric method was developed using Carbon Paste Electrodes (CPE) modified with Bismuth - and Fe3O4 Nanoparticles (CPE-Bi-Fe3O4) to increase the sensitivity in determine manganese level because it offers the advantages such as inexpensive, easy-to-manufacture, portable, inexpensive instrument, and does not require preparation sample before analysis. The bismuth precursor used was obtained from bismuth oxide which has obtained by heating Bi(OH)3 at 3250C for 3 hours. Magnetite is synthesized from a mixture of metal ion Fe2+ and Fe3+ with a ratio mole of 1:2. Modifiers were characterized using FTIR, SEMEDX, and XRD. Modified carbon paste electrodes were prepared by mixing modifier with mass ratio graphite:paraffin:Bi:Fe3O4 respectively of 6:3:1:1. Optimization of measurements carried out includes optimizing supporting electrolyte solutions, optimizing pH measurements, optimizing methods, optimizing potential and deposition time. Electrode performance tests were carried out in the form of scan rate tests, repeatability, and reproducibility tests, linearity tests and determination of detection limits, selectivity tests, and tests with samples. The most optimal measurements for metal ion Mn2+ measurements were obtained in a 0.1M acetate buffer electrolyte support pH 5 SWCSV method with a deposition potential of 700 mV and a deposition time of 60 s. The scan rate test results show that the diffusion process controls the redox reaction or electron transfer that occurs on the surface of the working electrode. One electrode repeatability test was carried out 30 times with a value of %RSD <% Horwitz RSD, namely 6,5751% < 7,3924%. The reproducibility test (n = 7) obtained a current response value that was not significantly different. The calibration curve shows a linear range at concentrations of 0,8 – 2,4 ?M and 2-10 ?M. The measurement detection limit obtained is 228,068 nM. Tests for ion interference were carried out on metal ion Mn2+ solutions using metal ion Fe2+, Cr3+ and Co2+ ions in a mole ratio of 1:10 and 1:100 result didn’t cause a change in current, so it was concluded that these ions didn’t interfere with current measurements on metal ion Mn2+. Tests on samples were carried out on 3 types of samples using the standard addition method to obtain concentrations of 89,1381; 89,1381; and 108,1857 ?M. The results obtained were then tested statistically with the t-test at a 95% confidence level and the null hypothesis (HO) was accepted. The results of sample testing were also compared with the AAS method as the standard method and statistically tested using paired t-tests. The statistical results of the t-test showed that the results of metal ion Mn2+ measurements using voltammetry did not differ from measurements using AAS at a 95% confidence level.